Our Experience with Stem Cell Applications in Patients with Advanced Peripheral Arterial Disease - Usta, Sefer (Journal of Clinical Nephrology, 2025)
Objective: To assess the results of stem cell applications in patients with peripheral arterial disease who could not undergo surgical treatment due to advanced-stage ischemia. Study design: Patients who could not undergo revascularization due to distal vascular insuffi ciency were recruited into this study between June 2009 and 2015. Stem cells obtained via bone marrow aspiration were utilized in 30 patients (17 male, 13 female; mean age, 56.2 y), and stem cells obtained from abdominal fat tissue were utilized in another 30 patients (22 male, 8 female; mean age, 58.9 y). Twenty patients with similar clinical symptoms who received medical treatment only comprised the control group for comparisons. Results: Stem cells were harvested from the bone marrow under local anesthesia, while general anesthesia was used for collecting stem cells of adipose tissue origin. Cells collected from each patient were processed in mobile units and were ready to use within approximately 1 hour. The harvested stem cells were administered percutaneously via intramuscular injections into the target tissues, conforming to vascular anatomy. Clinical status, ankle-brachial indices, pulse oximetry, and walking distance with exercise test were assessed at 1, 3, and 6 months after the procedures. Conclusion: Stem cell applications performed in patients unfeasible for revascularization appear to be associated with improvements in clinical symptoms, quality of life, and walking distance. We believe that this therapy may help reduce the rate of amputation